Enhancing Cybersecurity Risk Management Strategies in Financial Institutions: A Comprehensive Analysis of Threats and Mitigation Approaches - Agus Kristian; Achani Rahmania Az-Zahra; Farhan Hidayat; Ahmad Yadi Fauzi; Evelin Kallas (CORISINTA, 2024)
This study investigates the cybersecurity risks faced by financial institutions, with a particular focus on identifying common threats, evaluating their impact, and assessing the effectiveness of risk management strategies. Utilizing a mixed-methods approach, data were collected from both primary and secondary sources, including expert interviews, surveys, and a review of academic and industry literature. The results highlight that phishing, ransomware, and malware are among the most prevalent threats, with email and websites being the primary attack vectors. The study also examines the significant financial and reputational impacts these threats pose. A case study of XYZ Bank demonstrates how a layered approach to cybersecurity, involving prevention, detection, response, and recovery strategies, can substantially reduce the frequency of cyber incidents. The findings emphasize the importance of continuous updates to security policies, regular employee training, and investment in advanced security technologies. The study concludes with recommendations for financial institutions to enhance their cybersecurity posture through comprehensive risk management strategies.